1990
DOI: 10.1111/j.1600-0773.1990.tb00753.x
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical Effects of Two Low Osmolality Contrast Media, Ioxaglate and Iohexol, on Isolated Rat Atria

Abstract: This study aimed at investigating the direct effects of two low osmolality radiographic contrast media, iohexol (non-ionic) and ioxaglate (ionic), on transmembrane action potentials, contractile force and refractoriness of isolated rat atrial preparations. Superfused with 10% solution, ioxaglate induced a biphasic mechanical response, initially decreasing and thereafter increasing contractile force. The same concentration of iohexol only increased contractile force. The two contrast media increased the resting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…No study has, to our knowledge, been conducted on IRCM effects on the membrane potential of vascular smooth muscle. However, Kløw et al (14) and Tande et al (27) have shown that IRCM lower the membrane potential of myocardial cells, supporting our suggestion that IRCM evoke their vasodilator effects by hyperpolarizing smooth muscle. The recent finding by Bøyum and co-workers (4), that iohexol stimulates efflux of K + from monocytes, gives further support to this hypothesis.…”
Section: Discussionsupporting
confidence: 90%
“…No study has, to our knowledge, been conducted on IRCM effects on the membrane potential of vascular smooth muscle. However, Kløw et al (14) and Tande et al (27) have shown that IRCM lower the membrane potential of myocardial cells, supporting our suggestion that IRCM evoke their vasodilator effects by hyperpolarizing smooth muscle. The recent finding by Bøyum and co-workers (4), that iohexol stimulates efflux of K + from monocytes, gives further support to this hypothesis.…”
Section: Discussionsupporting
confidence: 90%
“…The short-lasting augmentation of Q R S duration a n d the shift in the Q R S axis by b o t h iohexol preparations in this study are probably d u e t o reduced velocity of intraventricular conduction a n d depolarization (12,23). T h e changes observed in the Q R S axis were on average less than 25° a n d smaller than t h e reported 30 t o 120° axis deviation found with high osmolar contrast media (8,15).…”
Section: Discussionmentioning
confidence: 52%
“…Disturbances in impulse formation may increase automaticity, but probably more important are the regional changes within the myocardium in impulse conduction and conductivity resulting in re-entry tachyarrhythmias (12,19). Thus, in the isolated myocardium iohexol has been shown to reduce the conductivity and shorten the effective refractory period despite prolonged action potential duration (12,23). …”
Section: Discussionmentioning
confidence: 99%